2021
DOI: 10.2147/ijgm.s324332
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Blood Glucose and Hemoglobin A1c Levels and Urinary Incontinence in Women

Abstract: Objective The purpose of this study was to evaluate the associations between blood glucose and hemoglobin A1c (HbA1c) levels with the degree of stress urinary incontinence (SUI) and urgency urinary incontinence (UUI) in women. Methods We conducted a cross-sectional study of female participants in the National Health and Nutrition Examination Survey (NHANES) database between 2007 and 2012. Univariate and multivariate logistic regressions were used to assess the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…This may be due to a discrepancy in patient populations where severity or control of diabetes may be different. Studies of non‐stroke female patients yielded conflicting findings, with some reported an increased risk of UI with poorer glycaemic control, as reflected by higher levels of glycated hemoglobin (HbA1c), 23,24 whilst others found no association 25,26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to a discrepancy in patient populations where severity or control of diabetes may be different. Studies of non‐stroke female patients yielded conflicting findings, with some reported an increased risk of UI with poorer glycaemic control, as reflected by higher levels of glycated hemoglobin (HbA1c), 23,24 whilst others found no association 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…13 This may be due to a discrepancy in patient populations where severity or control of diabetes may be different. Studies of nonstroke female patients yielded conflicting findings, with some reported an increased risk of UI with poorer glycaemic control, as reflected by higher levels of glycated hemoglobin (HbA1c), 23,24 whilst others found no association. 25,26 There exists a paucity of analysis on sex-specific risk factors for UI, our findings are therefore novel and revealed similar (although not identical) ORs for men and women in multivariable regression model.…”
Section: Key Findingsmentioning
confidence: 99%
“…Prevalensi UI tinggi dan meningkat sesuai dengan usia. Tingkat kejadian UI lebih tinggi pada pasien lanjut usia yang tinggal di panti jompo atau pasien yang mengalami demensia atau gangguan kognitif (Liu et al, 2021). Sekitar 77% perempuan lanjut usia yang tinggal dengan home care service memiliki inkontinensia urin (Batmani et al, 2021).…”
Section: Pendahuluanunclassified